Pengaruh Dukungan Sosial terhadap Konsep Diri Remaja Beresiko Tinggi di Panti Sosial Marsudi Putra “Toddopuli” Makassar - Rahman, Istianah A.; Ismail, Khaidzir; Sarnon, Norulhuda (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2018)
Rampant violations of legal and moral value samong teenagers, has sparked a number of children/adolescents who have to deal with the law. The devian behavioral phenomena occurs partly due to the lack adolescents develop self-concept because of the circumstances in the implementation of families that are less social support, Asone solution, it is very important to develop a high-risk adolescent self-concept. Similarly, self-concept, social support was greatly needed by teenagers. One thing that can help a person to develop a quality that is with strong social support. This study aims to determine the profile of high-risk adolescents and the influence of social support to high-risk adolescent self-concept. The study population was all adolescents PSMP beneficiaries in 2015 as many as 230 people. With the process of purposive sampling of 108 samples elected high-risk adolescents. Data were collected using the instrument scale social support and self-concept scale. Then the data were analyzed by using descriptive statistics and regression analysis. The study found several images of descriptive profiles of respondents and that there are significant social support to high-risk adolescent self-concept in PSMP Toddopuli Makassar. It is based on statistical results (R= 0105, R2= 0.011, F= 0.595, p= 0.043, p< 0.05). It can be concluded that social support is only an impact of 1.1% of self-concept. The implication of this study is that in forming a positive self concept one factor is the effective provision of social support, because there are still other factors.